A surprising diagnosis in a young patient with intermittent claudication: symptomatic isolated external iliac artery aneurysm associated with cystic media necrosis - Chatzantonis, Georgios; Schmoll, Lillian Gatwiri; Strübing, Felix; Chatzantonis, Grigorios; Kühner, Clemens (Journal of vascular surgery cases and innovative techniques, 2020)
Aneurysms of the external iliac artery are extremely rare. We present a case of a middle-aged male patient with calf claudication owing to peripheral arterial embolism on the basis of a thrombosed true aneurysm of the external iliac artery caused by cystic media necrosis. Vascular imaging established the diagnosis and we proceeded to removal of the aneurysm via open repair, with excellent surgical and clinical results.